Pemberdayaan Gereja dalam Pendampingan Perempuan Korban KDRT pada Jemaat Efata Liliba - Dethan, Mesakh Abia Pello; Ekon, Yanto Melkianus P.; Nuhamara, Melkianus (Universitas Muhammadiyah Surakarta, 2025)
The congregation of GMIT Efata Liliba is located in the Liliba neighborhood, approximately 5.4 kilometers away from Artha Wacana Christian University, with a travel distance of around 11-15 minutes by land. In recent years, women and children in this area have been experiencing domestic violence (KDRT). Furthermore, there has been a growing trend of such incidents each year, including among female pastors within the church. Recognizing the challenges faced by this partner community, the PkM UKAW team took the initiative to approach them and discuss related issues, such as: 1) The church has not yet found a theological solution to the problem where domestic violence is accepted as fate and destiny. 2) The church often encounters difficulties in providing pastoral support to KDRT victims. 3) Legal assistance for victims is still very limited because the church struggles to explain and provide legal counseling and advocacy to victims. Based on the previously discussed problems and proposed solutions with our partners, the following technological interventions will be implemented: (1) The importance of correct theological understanding for husbands or perpetrators to minimize KDRT actions. (2) Partners will be provided with knowledge and skills for pastoral counseling to assist them in addressing the difficulties in providing pastoral support to victims. (3) Partners will also be trained in how to provide legal assistance to KDRT victims. This solution is urgently needed to address community issues.